2019
DOI: 10.3390/nu11040801
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Validity, Reliability and Conceptual Alignment of Food Literacy Measures for Adults

Abstract: The measurement of food literacy has recently gained momentum globally. The aim of this paper is to review the literature in order to describe and analyse the measurement of adult food literacy. The objectives are to i) identify tools that explicitly measure food literacy in adults; ii) summarise their psychometric properties; and iii) critique tool items against the four domains and 11 components of food literacy, as conceptualised by Vidgen and Gallegos. Using the PRISMA guidelines, a search of seven databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 55 publications
0
53
0
2
Order By: Relevance
“…The following display of the study findings includes the contrast against current literature reported by Vidgen and Gallegos (Appendix A Table A1) [3,25], Thomas and colleagues (Appendix A Table A2) [12,13], and Truman and Elliott (Appendix B) [17]. To provide a clearer reading of the results, the components of these theoretical frameworks were numbered, as done previously by Amouzandeh and colleagues [25]; the inventory of the frameworks' categories and its respective attributes are detailed in the Appendices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following display of the study findings includes the contrast against current literature reported by Vidgen and Gallegos (Appendix A Table A1) [3,25], Thomas and colleagues (Appendix A Table A2) [12,13], and Truman and Elliott (Appendix B) [17]. To provide a clearer reading of the results, the components of these theoretical frameworks were numbered, as done previously by Amouzandeh and colleagues [25]; the inventory of the frameworks' categories and its respective attributes are detailed in the Appendices.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in addition to the majority of research originating from Canada and Australia, European studies focusing on food literacy are still scarce [24]. Northern and central European countries-specifically the United Kingdom, Italy, France, Netherlands, Switzerland, and Denmark-recently started to develop food-literacy-related research [24,25]. Particularly in Portugal, the ministry of health designated the National Program for the Promotion of Healthy Eating as one of the priority programs to be developed by governmental actions; this aims to improve the population's nutritional status by encouraging the availability and consumption of foods that integrate a healthy eating regime [26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, scoping reviews can be beneficial from both a research and practice perspective. To illustrate its use in the field of nutrition, Amouzandeh et al recently conducted a scoping review of the validity, reliability and conceptual alignment of food literacy measures for adults (5) . The authors concluded that most tools provided a theoretical framework, which is valid and reliable (5) .…”
Section: Scoping Reviewsmentioning
confidence: 99%
“…To illustrate its use in the field of nutrition, Amouzandeh et al recently conducted a scoping review of the validity, reliability and conceptual alignment of food literacy measures for adults (5) . The authors concluded that most tools provided a theoretical framework, which is valid and reliable (5) . In addition, they believed that their results will assist practitioners in selecting and developing tools for the measurement of food literacy (5) .…”
Section: Scoping Reviewsmentioning
confidence: 99%
See 1 more Smart Citation